Transfusion errors in the Thai anesthesia incidents study (THAI Study): Three cases - Somboon Thienthong (2018)
Of 163,403 recorded cases of anesthesia in the Thai Anesthesia Incidents Study (THAI Study), transfusion errors occurred thrice. Case°#1:° a 68-year-old male, blood group A, undergoing hepatectomy, received two units of PRC and four units of FFP (all units were group A), but two of the FFP units were given to the wrong patient because the caregiver did not check the patient-identification on all of the blood bags. Case #2: a 42-year-old female, blood group A, undergoing emergency exploratory laparotomy, received 250 mL of group B-blood. Skin rashes, a clue for diagnosis of transfusion error, were observed in the postoperative period. The error occurred because the caregiver did not check the patient-identification before starting the transfusion. Case #3: a 42-year-old female, blood group O, undergoing hysterectomy, received 430 mL of group AB-blood. More blood was requested in the ICU and it was discovered that the new bag was group O instead of AB. Mislabeling of the blood sample at the first blood request accounted for the error even though blood group O was r ecorded on the patient s OPD chart. The first two patients developed minor adverse reactions (grade 1) whereas the third developed a severe reaction (grade 3). All of the patients responded well to treatments. Accordingly, the system for preventing transfusion errors has been improved at both hospitals.